Characterizing the Composition of Sand and Mud Suspensions in Coastal and Estuarine Environments Using Combined Optical and Acoustic Measurements. Issue 7 (13th July 2021) - Pearson, Stuart G.; Verney, Romaric; van Prooijen, Bram C.; Tran, Duc; Hendriks, Erik C. M.; Jacquet, Matthias; Wang, Zheng Bing
Abstract: Quantifying and characterizing suspended sediment is essential to successful monitoring and management of estuaries and coastal environments. To quantify suspended sediment, optical and acoustic backscatter instruments are often used. Optical backscatter systems are more sensitive to mud particles (<63 μm) and flocs, whereas acoustic backscatter systems are more responsive to larger sand grains (>63 μm). It is thus challenging to estimate the relative proportion of sand or mud in environments where both types of sediment are present. The suspended sediment concentration measured by these devices depends on the composition of that sediment, thus it is also difficult to confidently measure concentration with a single instrument when the composition varies and extensive calibration is not possible. The objective of this paper is to develop a methodology for characterizing the relative proportions of sand and mud in mixed sediment suspensions by comparing the response of simultaneous optical and acoustic measurements. We derive a sediment composition index (SCI) that is used to directly predict the relative fraction of sand in suspension. Here, we verify the theoretical response of these optical and acoustic instruments in laboratory experiments and successfully apply this approach to field measurements from Ameland ebb‐tidal delta (the Netherlands). Increasing sand content decreases SCI, which was verified in laboratory experiments. A reduction in SCI appears during more energetic conditions when sand resuspension is expected. Conversely, the SCI increases in calmer conditions when sand settles out, leaving behind mud. This approach provides crucial knowledge of suspended sediment composition in mixed sediment environments. Plain Language Summary: Sand and mud particles are the building blocks of our coastlines. Counting and describing sand and mud particles floating through the water is essential to managing coasts. We commonly do this with devices that send out a sound (acoustic) or light (optical) signal into the water. The sensors measure the strength of the signal reflecting back off of any sand and mud particles passing by. Optical instruments are better at "seeing" mud than sand, and acoustic instruments are better at "hearing" sand than mud. If both sand and mud are present, a single instrument will not accurately estimate the total amount of sediment because of these different sensitivities. Instead, we can use both types of instrument together and compare what we "see" with what we "hear." This comparison allows us to estimate whether there are more sand or mud particles floating through the water. The relationship between "seeing" and "hearing" can be described in a single number, the sediment composition index (SCI). We successfully tested this approach in laboratory experiments and then applied it to a site on the coast of the Netherlands. This approach gives us a new way to understand environments that are both sandy and muddy. Key Points: Suspended sand and mud can be distinguished by their different optical and acoustic backscatter signatures We define a sediment composition index (SCI) from relative optical and acoustic backscatter and verify it with lab and field measurements SCI can be used to estimate the fraction of suspended sand, adding interpretive value to measurements in mixed sediment environments